Investigation of V2O5 and CeO2 Nanoparticles: Synthesis, Characterization, and Application in Ammonium Removal from Aqueous Solutions - Abdel-Zahra, Zainab J.; Rasheed, Rashed T.; Jweeg, Muhsin Jaber; Mohammed, M. N.; Abdullah, Thamer Adnan; Mohammed, Mais A.; Imarah, Ali O.; Abdullah, Oday I. (Engineering, Technology & Applied Science Research, 2025)
In this study, vanadium pentoxide (V2O5) and cerium dioxide (CeO2) nanoparticles were synthesized using hydrothermal and autoclave methods, respectively. The nanoparticles underwent thermal treatment at 90 °C and 400 °C, followed by structural and compositional analysis through X-Ray Diffraction (XRD). The surface morphology was examined using field emission Scanning Electron Microscopy (SEM), while Atomic Force Microscopy (AFM) was employed to assess the nanoscale surface roughness. The Fourier Transform Infrared Spectroscopy (FTIR) identified the functional groups, and the UV/Visible spectrometry evaluated their optical properties. The ammonium removal efficiency of the synthesized nanoparticles was also investigated. The results indicated that vanadium pentoxide exhibited the highest ammonium removal efficiency at 90 °C and 400 °C, with nanoparticles treated at 400 °C demonstrating enhanced performance compared to those treated at 90 °C.